Linguo-Didactic Fundamentals of Formation of Student Linguistic Competences in Teaching Kyrgyz Language as a Second Language in Higher Education Institutions (Through The Example of Legal Professions) - Sydykbaeva, Mira; Atabekova , Baktygul; Dzhalilova, Baktykan; Abdyrakhmanova, Akmaral (Journal of Ecohumanism, 2025)
The article is devoted to the problem of the formation of students’ language competencies when teaching Kyrgyz as a second language in higher educational institutions in Kyrgyzstan through the example of legal professions. The article gives a brief description of the concept of "language competence", considers the approaches of foreign and domestic scientists to the allocation of levels of formation of linguistic communicative competence.